Farmer's Decisions in Selecting Superior Shallot Seeds in Solok Regency West Sumatra - Tane, Conny Belinda; Tinaprilla, Netti; Purwono, Joko (Jurnal Manajemen dan Agribisnis, 2024)
Background: Shallots are a commodity that is exceptionally strategic and economical regarding farming profits. One way that farmers can increase production results is by adopting technology, such as using superior seeds. Purpose: This research aims to describe the implementation of the SOP for SS Sakato red onion farming, identify factors that influence farmers using superior SS Sakato seeds, and analyze differences in performance between shallot farmers who use SS Sakato seeds and Non SS Sakato seeds.Design/methodology/approach: The methods used are qualitative and quantitative analysis, logit regression analysis, and propensity score matching (PSM) analysis. Findings/Result: The results show that the SOP adoption rate for shallots is 82%, with the highest SOP adoption being plant maintenance and the lowest SOP adoption rate determining when to plant. Factors significantly influencing farmers' decisions to use superior SS Sakato seeds in Sungai Nanam are farmer education, farmer income, access to production facilities, agricultural extension, land area, and seed resistance to pests and diseases. The use of superior SS Sakato seeds significantly positively impacts shallot production and farmer profit in shallot farming. The use of superior SS Sakato seeds can increase the income of shallot farmers even though the costs of farming are higher. The use of superior seeds should be able to reduce the costs that farmers have to pay, but in this study, the costs incurred by farmers remained high.Conclusion: Increasing the productivity of shallots can be achieved by using quality seeds, using shallot varieties that are highly productive, adaptive, and resistant to pests and diseases, and improving cultivation techniques according to SOP. Farmers who use superior SS Sakato seeds should comply with the Standard Operating Procedure (SOP) to maximize shallot production. With an emphasis on increasing production, there should be support for farmers from seed breeding institutions to innovate in order to be able to provide superior seeds, support from technology-producing institutions, and support from extension services both from the government and the private sector.Originality/value (State of the art): This study describes that the use of superior seeds will impact the production and productivity of shallots, costs incurred by farmers, and farmer profits. Technology is an essential factor in influencing the production function; utilizing technology will have implications for increasing efficiency. Superior seeds are a technology that can have a long-term impact.Keywords: binary logit regression, propensity score matching (PSM), shallots, standard operating procedures (SOP), superior seeds